2009
DOI: 10.3892/or_00000292
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence diagnosis and flat lesions of urothelium: New challenges for pathologists and urologists (Review)

Abstract: Abstract. Bladder cancer is a common malignancy. Recurrence rate and progression vary greatly depending on factors such as tumor multiplicity, size, previous recurrence rates, tumor stage, tumor grade and the presence of carcinoma in situ. Treatment is expensive, recent studies demonstrated that superficial bladder cancer is a major economic burden. It is necessary to establish new kinds of techniques to improve diagnosis, therapy and follow-up, such as fluorescence diagnosis, without adding significant risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Indeed, several studies have shown an improvement in the overall diagnosis of bladder cancer, CIS, and other metaplastic, atypic, or dysplastic flat lesions [28,29], but the sensibility and specificity of fluorescence diagnosis to detect variant histology of urothelial carcinoma have never been assessed, leaving the problem currently unresolved. Indeed, several studies have shown an improvement in the overall diagnosis of bladder cancer, CIS, and other metaplastic, atypic, or dysplastic flat lesions [28,29], but the sensibility and specificity of fluorescence diagnosis to detect variant histology of urothelial carcinoma have never been assessed, leaving the problem currently unresolved.…”
Section: Underdiagnosis Of Nonmuscle Invasive Bladder Cancer With Varmentioning
confidence: 99%
“…Indeed, several studies have shown an improvement in the overall diagnosis of bladder cancer, CIS, and other metaplastic, atypic, or dysplastic flat lesions [28,29], but the sensibility and specificity of fluorescence diagnosis to detect variant histology of urothelial carcinoma have never been assessed, leaving the problem currently unresolved. Indeed, several studies have shown an improvement in the overall diagnosis of bladder cancer, CIS, and other metaplastic, atypic, or dysplastic flat lesions [28,29], but the sensibility and specificity of fluorescence diagnosis to detect variant histology of urothelial carcinoma have never been assessed, leaving the problem currently unresolved.…”
Section: Underdiagnosis Of Nonmuscle Invasive Bladder Cancer With Varmentioning
confidence: 99%